2010
DOI: 10.4149/neo_2010_03_264
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-181 family predicts response to concomitant chemoradiotherapy with temozolomide in glioblastoma patients

Abstract: MicroRNAs are endogenously expressed regulatory noncoding RNAs. Previous studies showed altered expression levels of several microRNAs in glioblastomas. In this study, we examined the expression levels of selected microRNAs in 22 primary glioblastomas and six specimens of adult brain tissue by real-time PCR method. In addition, we examined methylation status of MGMT promoter by methylation-specific real-time PCR, as this has been shown to be a predictive marker in glioblastomas. MGMT methylation status was not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
114
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(119 citation statements)
references
References 20 publications
3
114
0
2
Order By: Relevance
“…hsamiR-100 regulates the insulin-like growth factor 1 receptor/ mammalian target of rapamycin (IGF-1R/mTOR) pathway, which has an important role in the regulation of adrenocortical cell proliferation. 36 The upregulation of tissue hsa-miR181b has been previously described in ACC compared with ACA, 16,17 as well as in several cancers [38][39][40] Moreover, it was associated with poor prognosis in colon adenocarcinomas. 39 hsa-miR-181b behaves as a tumor suppressor, and can target important oncogenes such as B-cell lymphoma 2 (BCL2), 41 TIMP metallopeptidase inhibitor 3 (TIMP3) 42 and insulin-like growth factor 1 receptor (IGF1R).…”
Section: Plasma Micrornas In Adrenocortical Tumorsmentioning
confidence: 99%
“…hsamiR-100 regulates the insulin-like growth factor 1 receptor/ mammalian target of rapamycin (IGF-1R/mTOR) pathway, which has an important role in the regulation of adrenocortical cell proliferation. 36 The upregulation of tissue hsa-miR181b has been previously described in ACC compared with ACA, 16,17 as well as in several cancers [38][39][40] Moreover, it was associated with poor prognosis in colon adenocarcinomas. 39 hsa-miR-181b behaves as a tumor suppressor, and can target important oncogenes such as B-cell lymphoma 2 (BCL2), 41 TIMP metallopeptidase inhibitor 3 (TIMP3) 42 and insulin-like growth factor 1 receptor (IGF1R).…”
Section: Plasma Micrornas In Adrenocortical Tumorsmentioning
confidence: 99%
“…In their study, Yu et al report plasma levels of miR-21, miR-128 and miR-342-3p being altered in GBM patients compared with normal, healthy controls [14]. In addition, the observations of Slaby et al illustrate that there is a trend of downregulation of miRNA-181b and miRNA-181c in patients with better response to concomitant radiation therapy and TMZ, in comparison to those with disease progression [15]. Overall, there is much potential for the future use of miRNAs to augment current patient monitoring.…”
mentioning
confidence: 88%
“…Slaby et al. 88 also examined the correlation between expression levels of selected miRNAs and TMZ resistance in GBM, but used 22 primary GBM tumors instead of cell lines. They found that miR‐221, miR‐222, miR‐181b, miR‐181c, and miR‐128 were significantly downregulated with GBM, while miR‐21 was overexpressed.…”
Section: Introductionmentioning
confidence: 99%